Treatment strategy modification and its implication on the medical cost of fractional flow reserve-guided percutaneous coronary intervention in Japan. Issue 1 (January 2019) - Tanaka, Nobuhiro; Kohsaka, Shun; Murata, Tatsunori; Akasaka, Takashi; Kadota, Kazushige; Uemura, Shirou; Amano, Tetsuya; Shiode, Nobuo; Morino, Yoshihiro; Fujii, Kenshi; Hikichi, Yutaka; Nakamura, Masato
Highlights: The cost of tests was increased by 185, 660 JPY per patient by the addition of fractional flow reserve (FFR). The cost of treatment with percutaneous coronary intervention was reduced by 473, 012 JPY per patient. In scenario analysis, the cost reduction by FFR measurement was 109, 758 JPY. The one-way sensitivity analysis confirmed the robustness of this analysis. Abstract: Background: Fractional flow reserve (FFR)-guided percutaneous coronary intervention (PCI) could improve outcome compared with angiography-guided PCI. However, the economic impact of FFR-guided PCI remains largely unknown in the medical system in Japan. We evaluated the impact of treatment strategy modification by FFR measurement on the direct medical cost using a model analysis with a decision tree model in Japan. Methods: For the clinical parameters set in the model, the findings from CVIT-DEFER registry were adopted. Cost parameters were considered on the assumption that coronary angiography, FFR measurement, and the treatment are performed at Diagnosis Procedure combination (DPC) hospitals, and the costs were calculated based on the medical fee reimbursement systems in Japan. Results: The probability of deferral of PCI in patients who were allocated to PCI based on coronary angiography was set as 90.1% based on the CVIT-DEFER registry. In the model analysis, the cost of tests was increased by 185, 660 JPY per patient by the addition of FFR measurement, but the cost of treatment with PCI was reduced by 561, 425 JPY per patient, and the entire cost of treatment was reduced by 322, 675 JPY, resulting in the expected reduction in the total expected medical cost by 137, 015 JPY per patient. Conclusion: Under contemporary Japanese practice, FFR-guided PCI has potential to reduce the medical cost by effective reassessment of coronary stenosis and reducing inappropriate application of PCI.